PEMBERDAYAAN PETANI KOPI MELALUI PENGUATAN KELEMBAGAAN DI DESA KAONGKE-ONGKEA KECAMATAN PASARWAJO KABUPATEN BUTON - Edy, Safrin (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2018)
The objectives of this study are: (1) to describe the form of empowerment of farmer communities through the institutional strengthening of coffee farmers (2) to describe the model of farmer empowerment through institutional strengthening and (3) identify the obstacles encountered in empowering coffee farmers through institutional strengthening. The study was conducted in Kaongke Ongkea Village, Pasarwajo Subdistrict, Buton Regency in February - April 2017. The study was conducted using qualitative methods. The object of research is coffee farmers involved in coffee processing groups. Data collected through in-depth interviews with informants. The results showed that the form of empowerment of coffee farmers through strengthening institutional farmers, namely: a) increasing the capacity of Human Resources and strengthening farming capital, b) the model of empowering farmer communities through strengthening farmer institutions, namely: creating a social situation or climate, strengthening the potential or power owned by farmers and protect from all their weaknesses, c) obstacles encountered in empowering farmers through institutional strengthening, among others: internal constraints namely: limited human resources, especially farmers and limited budgets at the farm level in developing farming. Afterwhile is an external obstacle, which is not yet established a good partnership between farmers.   Keywords: Empowerment, strengthening, institutions, food barns, farmers